## Re: [PrimeNumbers] Re: Pell Equation

Expand Messages
• ... no : the 3rd equation is wrong. M. [Non-text portions of this message have been removed]
Message 1 of 5 , Jun 23, 2013
• 0 Attachment

> **
> Kermit Rose <kermit@...> wrote:
> > if
> > a1^2 - d b1^2 = 1
> > a2^2 - d b2^2 = 1
> > then
> > (a1^2 + d b1^2)^2 - (2 d a1 b1)^2 = 1
> > (a1 a2 + d b1 b2)^2 - d (a1 b2 + b1 a2)^2 = 1
>
> Indeed.
>

no : the 3rd equation is wrong.

M.

[Non-text portions of this message have been removed]
• On 6/24/2013 12:07 PM, Maximilian Hasler ... (a1^2 + d b1^2)^2 - (2 d a1 b1)^2 = 1 should have been (a1^2 + d b1^2)^2 - d (2 a1 b1)^2 = 1 Kermit
Message 2 of 5 , Jun 24, 2013
• 0 Attachment
On 6/24/2013 12:07 PM,

"Maximilian Hasler"

wrote:
> ________________________________________________________________________
> 1a. Re: Pell Equation
> Posted by: "Maximilian Hasler" maximilian.hasler@... maximilian_hasler
> Date: Sun Jun 23, 2013 12:37 pm ((PDT))
>
>
>> **
>> Kermit Rose <kermit@...> wrote:
>>> if
>>> a1^2 - d b1^2 = 1
>>> a2^2 - d b2^2 = 1
>>> then
>>> (a1^2 + d b1^2)^2 - (2 d a1 b1)^2 = 1
>>> (a1 a2 + d b1 b2)^2 - d (a1 b2 + b1 a2)^2 = 1
>>
> no : the 3rd equation is wrong.
>
> M.
>

(a1^2 + d b1^2)^2 - (2 d a1 b1)^2 = 1

should have been

(a1^2 + d b1^2)^2 - d (2 a1 b1)^2 = 1

Kermit
Your message has been successfully submitted and would be delivered to recipients shortly.